Predicting and correcting ataxia using a model of cerebellar function. (7th May 2014) - Bhanpuri, Nasir H.; Okamura, Allison M.; Bastian, Amy J.
Abstract : Is cerebellar dysmetria due to a malfunctioning internal dynamic model? By applying forces to the arms of patients via a robotic exoskeleton, Bhanpuri et al . identify patient-specific deficits in reaching performance, and produce improvements in movement accuracy. Mathematical models reveal that bias in ataxic movements can be explained by an internal misestimate of arm inertia. Abstract : Cerebellar damage results in uncoordinated, variable and dysmetric movements known as ataxia. Here we show that we can reliably model single-joint reaching trajectories of patients ( n = 10), reproduce patient-like deficits in the behaviour of controls ( n = 11), and apply patient-specific compensations that improve reaching accuracy ( P < 0.02). Our approach was motivated by the theory that the cerebellum is essential for updating and/or storing an internal dynamic model that relates motor commands to changes in body state (e.g. arm position and velocity). We hypothesized that cerebellar damage causes a mismatch between the brain's modelled dynamics and the actual body dynamics, resulting in ataxia. We used both behavioural and computational approaches to demonstrate that specific cerebellar patient deficits result from biased internal models. Our results strongly support the idea that an intact cerebellum is critical for maintaining accurate internal models of dynamics. Importantly, we demonstrate how subject-specific compensation can improve movement in cerebellar patients, who are notoriously unresponsive to treatment.